Exploring factors predicting Diabetes Distress in patients with type 2 diabetes - Susanti, Yuli; Subrata, Sumarno Adi; Hudiyawati, Dian (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Diabetes mellitus, a chronic disease resulting from an impaired endocrine system, disrupts glucose regulation and leads to elevated blood glucose levels. Individuals with diabetes may develop complications such as hyperglycemia. Persistent hyperglycemia can negatively affect mental well-being, potentially causing depression, anxiety, and diabetes distress. While numerous studies have explored predictors of diabetes distress, their findings have been inconsistent, and a comprehensive understanding of the contributing risk factors remains elusive. Purpose: To identify the dominant factors influencing the occurrence of diabetes distress. Method: This quantitative descriptive study involved a sample of 150 respondents. Participants were included if they had a diagnosis of type 2 diabetes mellitus, were male or female, and were over 20 years of age, regardless of whether they had diabetes-related complications. Patients with unstable hemodynamic status or those unable to communicate effectively were excluded. The study took place at the Surakarta Islamic Hospital between July and September 2024. Data collection utilized demographic questionnaires, the Diabetes Distress Scale, the Hensarling Diabetes Family Support Scale, and the Medication Adherence Rating Scale. Pearson's test and multiple linear regression were used for data analysis. Results: The study found that the majority of respondents had a mean age of 56 years and were male. The analysis revealed four factors influencing diabetes distress in patients with Type 2 Diabetes Mellitus including treatment regimen (p-value = 0.001, B = -10.792), education level (p-value = 0.042, B = -3.779), age (p-value = 0.015, B = -0.404), and family support (p-value = 0.034, B = -0.333). Conclusion: The treatment regimen emerged as the most significant factor influencing diabetes distress; consistent adherence to the prescribed treatment plan was associated with lower levels of distress among individuals with type 2 diabetes mellitus. Furthermore, education level, age, and family support were identified as additional factors contributing to diabetes distress.